NbN superconducting nanowire single-photon detector with an active area of 300 μm-in-diameter - Chengjun Zhang (AIP Advances, 2019)
Superconducting nanowire single-photon detectors (SNSPDs) with both an ultra-large-active area and a high count rate (CR) are challenging from the design and fabrication. Here, we develop a NbN SNSPD with a circular active area of 300 μm-in-diameter and use multiple approaches to boost the maximal count rate (MCR). This large-active-area SNSPD is divided into nine pixels (parts). Each pixel consists of serially connected two superconducting nanowire avalanche photodetectors (SC-2SNAP), which yielded a four-fold reduction in the kinetic inductance of a single pixel. To further increase MCR, an optimized series resistance of about 380 Ω is added to each pixel, reducing the full recovery time of each pixel from a few microseconds to approximately 90 ns. All nine pixels show uniform superconducting critical temperatures of ∼7.4 K and switching currents in the range of 15.3–16.7 μA. When the detector coupled to a single-mode fiber and illuminated with 1064-nm photons, the single-pixel exhibits a well-saturated system detection efficiency (SDE) of 67% at a dark CR of 30 Hz, and its CR exceeds 10 MHz with an SDE of 50%. When coupled to a 200-μm multi-mode fiber, the total SDE of nine pixels is approximately 42% and the total MCR exceeds 43 MHz.